2023
DOI: 10.1039/d3sc03240j
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature ionic liquids with two symmetric ions

Daniel Rauber,
Frederik Philippi,
Daniel Schroeder
et al.

Abstract: Room temperature ionic liquids typically contain asymmetric organic cations. The asymmetry is thought to enhance disorder, thereby providing an entropic counter-balance to the strong, enthalpic, ionic interactions, and leading, therefore,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Symbols: solid, ammonium salts; open, phosphonium salts; black, cation–anion; blue, cation–cation; red, anion–anion; the lines are simply guides for the eye. Ionic liquids, left to right, with data sources: ammonium, [N (2O1)3,1 ]­[TFA], [N 4441 ]­[TFA], [N (2O1)3,1 ]­[FSI], [N 4441 ]­[FSI], [N (2O1)3,1 ]­[TSAC], [N 4441 ]­[TSAC], [N (2O1)3,1 ]­[Tf 2 N], [N 4441 ]­[Tf 2 N], [N 122,2O1 ]­[Tf 2 N], , [N 112,2O2O1 ]­[Tf 2 N], [N 1127 ]­[Tf 2 N], [N 112,2OCO1 ]­[Tf 2 N], [N (2O1)3,1 ]­[BETI], [N 4441 ]­[BETI], [N 1125 ]­[Tf 2 N], [C 2 TMEDA]­[Tf 2 N], [C 2 dmppz]­[Tf 2 N], [chol]­[Tf 2 N]; phosphonium: [P (3O1)4 ]­BF 4 , [P (3O1)4 ]­PF 6 , [P 5555 ]­PF 6 , [P (3O1)4 ]­[Tf 2 N], [P 5555 ]­[Tf 2 N], [P 222,8 ]­[Tf 2 N] 20 and [P 222,5 ]­[Tf 2 N] . The ion names corresponding to the abbreviated forms used here are given in Table S6 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Symbols: solid, ammonium salts; open, phosphonium salts; black, cation–anion; blue, cation–cation; red, anion–anion; the lines are simply guides for the eye. Ionic liquids, left to right, with data sources: ammonium, [N (2O1)3,1 ]­[TFA], [N 4441 ]­[TFA], [N (2O1)3,1 ]­[FSI], [N 4441 ]­[FSI], [N (2O1)3,1 ]­[TSAC], [N 4441 ]­[TSAC], [N (2O1)3,1 ]­[Tf 2 N], [N 4441 ]­[Tf 2 N], [N 122,2O1 ]­[Tf 2 N], , [N 112,2O2O1 ]­[Tf 2 N], [N 1127 ]­[Tf 2 N], [N 112,2OCO1 ]­[Tf 2 N], [N (2O1)3,1 ]­[BETI], [N 4441 ]­[BETI], [N 1125 ]­[Tf 2 N], [C 2 TMEDA]­[Tf 2 N], [C 2 dmppz]­[Tf 2 N], [chol]­[Tf 2 N]; phosphonium: [P (3O1)4 ]­BF 4 , [P (3O1)4 ]­PF 6 , [P 5555 ]­PF 6 , [P (3O1)4 ]­[Tf 2 N], [P 5555 ]­[Tf 2 N], [P 222,8 ]­[Tf 2 N] 20 and [P 222,5 ]­[Tf 2 N] . The ion names corresponding to the abbreviated forms used here are given in Table S6 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…As we have determined DDC for many ionic liquids with various cations and anions, including the three [BMIM] + -containing IL, and a number at high pressure, it is possible to use these to examine the conclusions of Ahmed et al in some detail. To extend the range of systems, we include DDC calculated from the transport properties measured by the Rauber group for certain ammonium and phosphonium ion-based ILs, our previously published DDC for certain high temperature molten salts, , and some protic ionic liquids based on the 1,8-diazabicyclo[5.4.0]­undec-7-ene cation ([DBUH] + ). …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, using ionic liquids (ILs) as surfactants have been studied, as their properties may be modified by changing their cation or anion type 23 , 24 . ILs are low-temperature molten salts that are fully constituted of anions and cations near room temperature 25 . Wilkes and Zaworotko 26 produced 1-ethyl-3-methylimidazolium tetrafluoroborates in the 1990s, and it was stable in both air and water.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] This effect has been reported since the 2000s, and even in recent years, various literature have been published describing the development of new RTILs with ether functional groups and the analysis of their physicochemical properties. [9][10][11][12][13][14][15] Rauber et al reported that the development of RTILs composed of symmetric cation with ether group and symmetric anion. 14 Warrington et al investigated the introduction effect of ether group into piperidinium and morpholinium cations on their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Rauber et al reported that the development of RTILs composed of symmetric cation with ether group and symmetric anion. 14 Warrington et al investigated the introduction effect of ether group into piperidinium and morpholinium cations on their physicochemical properties. 15 Understanding the structure-physicochemical properties correlation and properties as an electrolyte of ether-functionalized RTILs is quite important for the creation of the next generation of RTILs.…”
Section: Introductionmentioning
confidence: 99%